1996
DOI: 10.1172/jci118764
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine modulates vasomotor tone in outer medullary descending vasa recta of the rat.

Abstract: Adenosine is generated within the renal medulla under hypoxic conditions and is known to induce net vasoconstriction within the renal cortex while increasing medullary blood flow and oxygenation. To test the hypothesis that vasoconstriction of outer medullary descending vasa recta (OMDVR) is modulated by adenosine, we examined the effects of adenosine and adenosine A 1 and A 2 receptor subtype agonists on in vitro perfused control and preconstricted rat OMDVR. Constriction with angiotensin II (ANG II, 10 Ϫ 9 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…Pretreatment of medullary tissue strips with the P2 receptor antagonist suramin (albeit it is a relatively nonspecific antagonist) substantially blunted the cross talk from mTAL (141), indicating a role for P2Y or P2X receptors in the regulation of MBF (11). ATP and related nucleotides and PGE are known to be released in the renal outer medulla (8,14,23,60,102,148,172,173). Although it has been found that exogenous ATP stimulates pericytes and constricts VR (36), the complex role played by ATP and adenosine in the in vivo regulation of MBF and in tubulovascular cross talk remains to be explored.…”
Section: Excess O 2 ·ϫ and H 2 O 2 Production Relative To No In Mtal mentioning
confidence: 99%
“…Pretreatment of medullary tissue strips with the P2 receptor antagonist suramin (albeit it is a relatively nonspecific antagonist) substantially blunted the cross talk from mTAL (141), indicating a role for P2Y or P2X receptors in the regulation of MBF (11). ATP and related nucleotides and PGE are known to be released in the renal outer medulla (8,14,23,60,102,148,172,173). Although it has been found that exogenous ATP stimulates pericytes and constricts VR (36), the complex role played by ATP and adenosine in the in vivo regulation of MBF and in tubulovascular cross talk remains to be explored.…”
Section: Excess O 2 ·ϫ and H 2 O 2 Production Relative To No In Mtal mentioning
confidence: 99%
“…Studies in the isolated in vitro perfused outer medullary descending vasa recta (OMDVR) revealed that abluminal adenosine application causes vasoconstriction at low concentrations (10 pM to 0.1 M), whereas high concentrations (1-10 M) reversed the vasoconstriction (307). These vessels of the OMDVR are equipped with adenosine A 1 and A 2a /A 2b receptors (176) consistent with the notion that low adenosine concentrations caused vasoconstriction via the adenosine A 1 receptors, whereas higher concentrations can vasodilate via adenosine A 2 receptors.…”
Section: Effects Of Intrarenal Administration Of Adenosine On Renal Bmentioning
confidence: 99%
“…The mTAL has the capacity to produce adenosine (9) and that A 1 and A 2 receptor mRNA is expressed in DVR (54). Adenosine A 1 and A 2 receptor stimulation favors DVR vasoconstriction and vasodilation, respectively (144,145).…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%